PICK1 Genetic Variation and Cognitive Function in Patients with Schizophrenia - Yi-Ting Chen; Chieh-Hsin Lin; Chiung-Hsien Huang; Wen-Miin Liang; Hsien-Yuan Lane (Scientific Reports, 2017)
Abstract The gene of protein interacting with C kinase 1 alpha (PICK1) has been implicated in schizophrenia, nevertheless, conflicting results existed. However, its role in cognitive function remains unclear. Besides, cognitive deficits impair the long-term outcome. We explored whether the polymorphisms of PICK1 (rs2076369, rs3952) affected cognitive functions in schizophrenic patients. We analyzed 302 patients and tested the differences of cognitive functions, clinical symptoms between genetic groups. We also used general linear model to analyze the effect of PICK1 genetic polymorphisms on cognitive functions. After adjustment for gender, age, education, the patients with rs2076369 G/T genotype showed better performance than T/T homozygotes in the summary score, global composite score, neurocognitive composite score, category fluency subtest, WAIS-III-Digit Symbol Coding subtest, working memory, WMS-III-Spatial Span (backward) subtest, MSCEIT-managing emotions branch (p = 0.038, 0.025, 0.046, 0.036, 0.025, 0.027, 0.035, 0.028, respectively). G/G homozygotes performed better than T/T in category fluency subtest (p = 0.049). A/A homozygotes of rs3952 performed better than G/G in trail making A subtest (p = 0.048). To our knowledge, this is the first study to indicate that PICK1 polymorphisms may associate with cognitive functions in schizophrenic patients. Further replication studies in healthy controls or other ethnic groups are warranted.